Evolution of Orexin Neuropeptide System: Structure and Function - Soya, Shingo; Sakurai, Takeshi (Frontiers in Neuroscience, 2020)
Orexins are hypothalamic neuropeptides that were initially identified in the rat brain as endogenous ligands for an (previously) orphan G protein coupled receptor. They are multi-tasking peptides involving in many physiological functions, including regulation of feeding behavior, wakefulness and autonomic/neuroendocrine functions, and sleep/wakefulness states in mammals. There are two isopeptides of orexin, orexin A and orexin B, which are produced from a common precursor peptide, prepro-orexin. Structures of orexins, as well as orexin genes, are highly conserved throughout mammalian species, suggesting strong evolutionary pressure that maintains the structures. Their lengths and structure suggested that orexin B is the ancestral form of orexin neuropeptide. In mammals, orexins bind to two subtypes of G-protein coupled receptors, i.e., orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R). Phylogenetically, the orexin system is present exclusively in vertebrates. In genomes of species outside mammals, there is only one orexin receptor, which is similar to OX2R, suggesting that OX2R is the prototype receptor for orexins. OX1R is likely to have evolved during early mammalian evolution. Orexin-producing neurons (orexin neurons) are mainly located in the lateral hypothalamic area (LHA) in mammals and are also found in hypothalamic regions in many other vertebrates. Orexins are likely to be closely related to the regulation of active, motivated behavior in many species. The orexin system seems to have evolved as a system that supports active and purposeful behavior which is closely related with wakefulness.